Metastable to stable phase transformation in atmospheric plasma sprayed Yb-silicate coating during post-heat treatment. (1st March 2023) - Bakan, Emine; Sohn, Yoo Jung; Vaßen, Robert
Abstract: Yb-silicate is used as volatilization barrier material in environmental barrier coating applications. In this study, metastable to stable phase transformation in highly amorphous atmospheric plasma sprayed Yb-silicate coating was investigated during post-heat treatment. High-temperature X-ray diffraction (HT-XRD) was used to analyze the phase composition of the coating at elevated temperatures. Three metastable phases (Yb2 Si2 O7 ( P -1), Yb2 SiO5 ( P 21 / c ), Yb4.67 Si3 O13 ( P 63 / m )) and two stable phases (Yb2 Si2 O7 ( C 2/ m ), Yb2 SiO5 ( I 2/ a )) preferentially crystallized from the amorphous coating starting at 1000 °C. Metastable phases transformed into stable Yb2 Si2 O7 and Yb2 SiO5 at higher temperatures. HT-XRD data were used to estimate the volume expansion in the coating due to the phase transformation and the results were compared to the dilatometry measurements. The estimated expansion from HT-XRD data was larger than the measured expansion in dilatometry. Microstructural investigation revealed crack healing in the coating during the measurements which was associated with the lower expansion measured in dilatometry. Graphical abstract: Image, graphical abstract